REPRESENTAÇÕES POÉTICAS DAS ÁGUAS AMAZÔNICAS - Fares, Josebel Akel (Organon, 2007)
This article argument is centered in the construction of the Amazonian representations, based on the water metaphors. I present a repertoire of texts of the oral and written literature, to expound the aquonarratives – a term used by the professor Paulo Nunes (2001), concerning the works of the writer Dalcídio Jurandir. Thus, I begin by the water images in Caminha’s letter – “ Waters are so much: infinite” – and I go on the exposition with the metaphors of the river as Amazonic ruin, by Euclides da Cunha (1999), the river slaves, by Edison Carneiro (1946), the water dictatorship, by Giovanni Gallo (1980), the water as Amazonic clock, by Raymundo Morais (1936), the water nation, by Tiago Mello (2002), the river as a street, by Ruy Barata (ano?). And still, the cosmogonies which translate the inescapable condition of the waters, as the narratives of toco, listened in Marajó island, and the pororoca origin.